Levothyroxine Overdose in a Toddler – A Case Report - Thiyagarajan, Radha; Arunprasath, Thasma Santhanakrishnan (Journal of Nepal Paediatric Society, 2021)
Levothyroxine tablet overdose, can happen in children, because of unique physical nature of the tablet. Although it has a benign course, systemic symptoms of overdose may manifest in few children. This cannot be predicted based on dose consumed or by thyroid function tests. Propranolol and steroid can be used for systemic autonomic symptoms. Delayed manifestation of overdose may occur, which needs follow up. In this report, we present a toddler who had levothyroxine overdose and was managed with monitoring and follow up. Her hyperactivity was managed with oral triclofos. We would also like to emphasize that serial thyroid function tests are not needed in these children.